Links between maternal employment and child nutrition in rural Tanzania - Bethelhem Legesse Debela; Esther Gerke; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2019)
Child undernutrition remains a widespread problem in many developing countries. The empowerment of women, and mothers in particular, was shown to improve child nutrition in various geographical contexts. One important avenue to empower women is fostering female employment. However, maternal employment can influence child nutrition through different mechanisms; it is not clear under what conditions the overall effect will be positive. We develop a theoretical model to show that maternal employment can affect child nutrition through changes in (i) income, (ii) intra-household bargaining power, and (iii) time available for childcare. The links are empirically analyzed using panel data from rural Tanzania and regression models with maternal fixed effects. Maternal employment has non-linear effects on child height-for-age z-scores (HAZ), the standard indicator of longterm child nutritional status. Off-farm employment reduces child HAZ at low levels of labor supply. The effect turns positive at higher levels of off-farm labor supply and negative again at very high levels. The child nutrition effects of maternal time allocation to agricultural work on the own family farm are weaker than those of off-farm employment and statistically insignificant. These findings can help to better design development interventions that foster synergies and avoid potential tradeoffs between female empowerment and child nutrition goals.
Keywords: 330